A Metal–Organic Framework Based Methane Nano‐trap for the Capture of Coal‐Mine Methane. Issue 30 (22nd May 2019) - Niu, Zheng; Cui, Xili; Pham, Tony; Lan, Pui Ching; Xing, Huabin; Forrest, Katherine A.; Wojtas, Lukasz; Space, Brian; Ma, Shengqian
Abstract: As a major greenhouse gas, methane, which is directly vented from the coal‐mine to the atmosphere, has not yet drawn sufficient attention. To address this problem, we report a methane nano‐trap that features oppositely adjacent open metal sites and dense alkyl groups in a metal–organic framework (MOF). The alkyl MOF‐based methane nano‐trap exhibits a record‐high methane uptake and CH4 /N2 selectivity at 298 K and 1 bar. The methane molecules trapped within the alkyl MOF were crystalographically identified by single‐crystal X‐ray diffraction experiments, which in combination with molecular simulation studies unveiled the methane adsorption mechanism within the MOF‐based nano‐trap. The IAST calculations and the breakthrough experiments revealed that the alkyl MOF‐based methane nano‐trap is a new benchmark for CH4 /N2 separation, thereby providing a new perspective for capturing methane from coal‐mine methane to recover fuel and reduce greenhouse gas emissions. Abstract : It's a nano‐trap ! A MOF‐based methane nano‐trap that features oppositely adjacent open metal sites is proposed for capturing methane from CMM. The nano‐trap has a record‐high methane uptake at ambient pressure and a new benchmark for CH4 /N2 separation. The binding mechanism was investigated by single‐crystal X‐ray diffraction experiments and molecular simulation studies.